2019
DOI: 10.1097/ico.0000000000001846
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Donor Cornea Endothelial Cell Density Determined by Eye Banks and by a Central Reading Center in the Cornea Preservation Time Study

Abstract: Purpose: To evaluate agreement between eye banks (EBs) and a reading center on endothelial cell density (ECD) determinations in the Cornea Preservation Time Study. Methods: The Cornea Image Analysis Reading Center (CIARC) performed variable frame image analysis on EB-obtained–preoperative central endothelial images (after lamellar dissection for Descemet stripping automated endothelial keratoplasty by the EBs or before shipping, if surgeon prepared) to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 29 publications
1
12
1
Order By: Relevance
“…This is evidenced by the estimated difference in mean ECD after adjustment for these factors with a linear mixed model which was clinically indistinguishable from the difference calculated using an unadjusted paired t test. These results are consistent with findings in the SMAS 11 and CPTS, 10 which reported no effect on relative ECD difference when adjusting for donor history of diabetes and polymegethism/pleomorphism. The SMAS and CPTS also found no difference in relative ECD difference after adjusting for cause of donor death and the presence of stromal edema.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…This is evidenced by the estimated difference in mean ECD after adjustment for these factors with a linear mixed model which was clinically indistinguishable from the difference calculated using an unadjusted paired t test. These results are consistent with findings in the SMAS 11 and CPTS, 10 which reported no effect on relative ECD difference when adjusting for donor history of diabetes and polymegethism/pleomorphism. The SMAS and CPTS also found no difference in relative ECD difference after adjusting for cause of donor death and the presence of stromal edema.…”
Section: Discussionsupporting
confidence: 89%
“…Previously reported data from the CPTS from multiple eye banks and varying training and image analysis techniques found that the mean difference between eye bank–determined and CIARC-determined preoperative ECD was 15 cells/mm 2 . 10 The same study reported that eye bank–determined preoperative ECD was within 10% of the CIARC-determined ECD for 69% of the image sets (886 of the 1286 image sets). 10 A similarly performed study published in 2005, the SMAS, determined that the mean eye bank–determined screening ECD was 100 cells/mm 2 higher than the CIARC, with mismatch increasing as the image quality worsened.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The Cornea Donor Study (CDS) examined the accuracy of eye bank measurements in their data set and found most eye bank measurements fell within 10% of an established study reading center with image quality contributing to variability . The more recent Cornea Preservation Time Study (CPTS) also compared endothelial cell–density measurements between eye banks and a central reading center, finding measurements to be similar but with high variability between individual measurements …”
Section: Introductionmentioning
confidence: 99%